EFFECTS OF SOAKING AND COOKING ON PHYSICAL CHARACTERISTICS, TANNIN CONTENTS AND PROTEIN DIGESTIBILITY OF KIDNEY BEANS (PHASEOLUS VULGARIS L.) (Biological Sciences - PJSIR, 1996)
This study reports the effects of soaking and cooking methodson some physical characteristics, tannin contents and in vitro proteindigestibility of kidneybeans. Soakingofkidney beans insodium bicarbonate solutiongave rise to lower hydration capacity, hydrationindex, swellingcapacityandcookingtime than soaking insimple wateror neutral sodiumchloride solution.Tannin contentsofredkidneybeanswerereducedby soaking at30° and 100°Cfordifferent periods. However, soaking in sodium bicarbonate solution with or without sodium chloride was more efficient in reducing tannin contents. Maximum improvement in proteindigestibility was also observed by soaking kidney beans in mild alkaline solutions. Tannin contents were further reduced alongwith improvement in protein digestibility as a result of cooking.